Etnopedagogi Islami: Transformasi Nilai Budaya dalam Pembelajaran Sastra - Puri Lestari, Tusina (Andragogia: Journal Education Science And Islamic Studies, 2026)
This research explores the concept of Islamic ethnopedagogy as a strategy for transforming cultural values in literary learning at schools. The primary focus of this study is how the integration of local wisdom aligned with Islamic principles can strengthen students' character. Using a library research method, this study analyzes various literatures related to Nusantara's local wisdom, Islamic educational theory, and literary learning methodologies. The results show that regional literature is not merely a cultural artifact but a pedagogical medium containing values of Tawhid, Akhlaq, and Muamalah. This transformation is achieved through the reinterpretation of literary texts within the framework of Islamic values (Islamization of local knowledge) to address the challenges of moral decadence in the digital era. In conclusion, Islamic ethnopedagogy is capable of creating literary learning that is contextual, religious, and relevant to the nation's cultural identity.